Carbon content loss and recovery processes in aerial biomass in the forested areas of the Nevado de Toluca Flora and Fauna Protected Natural Area during the period 2000-2013 - Regil-García, Héctor Hugo (2019)
The temperate forests of México are under strong pressure both by biological processes and by anthropic exploitation, even if they belong to Protected Natural Areas (PNA). For the evaluation of these ecosystems and their deterioration processes, there are no control mechanisms that guarantee an improvement in their internal dynamics; therefore, land occupation studies are essential to understand these processes, particularly in the arboreal stratum, and their role in carbon capture and storage (C). The biomass and the C content per hectare of predominant forest species (Pinus hartwegii, Abies religiosa, Quercus laurina and Alnus jorullensis) were calculated from representative data from 30 land plots. The carbon stock assessment of each forest area was estimated from data of tree density per hectare, species dominance, basic wood density and biomass expansion factors. Carbon stock maps were superimposed (2000 and 2013) to obtain the areas presenting carbon stock variation processes. The forests with the highest loss of carbon (C) are those were Pinus hartwegii and Abies religiosa are the predominant species. Keywords: Land occupation; Aerial biomass; Carbon content; Deterioration.